Powstanie i funkcjonowanie Bogatyńskiej Kolei Dojazdowej w konsekwencji zmiany granic po II wojnie światowej - Jakuboszczak, Paweł (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
The article presents the functioning of Bogatynia Local Railway, which came into being through the division of Saxon Narrow-Gauge Railway (Sächsische Schmalspurbahn Zittau – Hermsdorf) as a result of border changes following World War II. The new territorial division caused creation of three separate railway lines within the borders of Czechoslovakia, German Democratic Republic (until 1949 – Soviet Occupation Zone of Germany) and Poland. The cross-border rail traffic between Germany and Czechoslovakia did not use these lines anymore.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne